Results-based approaches in agriculture: what is the potential? - Heiner Janus; Sarah Holzapfel (Deutsches Institut für Entwicklungspolitik (DIE), 2016)
Increased and more effective public and private investments in the agricultural sector are needed to address the challenge of ending hunger and achieving food security by 2030. This paper analyses the potential of results-based approaches – an innovative financing instrument that links payments to predefined results – to contribute to this challenge. Results-based approaches promise several potential advantages over traditional aid modalities, such as a greater focus on results, better accountability systems and improved incentives that increase aid effectiveness. They are also discussed as an important tool to accelerate innovation and to leverage additional resources from private investors for agricultural and food security interventions. Although widely applied in the health and education sectors, there are only a few experiences with results-based approaches in the agricultural sector, and the suitability of the sector for the instrument is debated. The aim of this paper is to contribute to this debate by reviewing three pilot interventions representing different types of results-based approaches: results-based aid (contract between governments), results-based finance (contract between a funder/host-country government and a service provider/company) and development impact bonds (contract between a funder, service provider and private investor). The analysis draws on existing literature on results-based approaches, expert interviews as well as on programme and guidance documents by various development agencies. The three interventions are compared based on three dimensions that have been shown in the literature to be important building blocks of results-based approaches. These are (1) selecting measurable results (2) setting up payment and verification mechanisms and (3) providing support to the incentivised actor. In addition, the potential and limitations of each pilot are assessed towards dealing with external factors influencing results, such as climate variability, addressing the complexities of different rural worlds – ranging from large-scale agro-economic companies to the landless poor – and the prospects for scaling-up. The analysis shows that results-based approaches have the potential to foster innovation in agriculture and can play an important role to increase food security in developing countries. Results-based aid programmes can provide additional incentives for partner country governments to focus on reducing hunger and malnutrition in the long run. Results-based finance programmes – by offering economic incentives to service providers or private companies – can help to overcome market failure and foster the adoption of new technologies. Development impact bonds are an innovative way to engage private actors in addressing development challenges. However, we also find that the agricultural sector poses additional challenges for implementing results-based approaches. For example, paying for results is more difficult in agriculture than in many other sectors. Desired outcomes such as increased yields or incomes are highly variable and influenced by external conditions (e.g. weather and world market prices). Intermediate outcome or output indicators, such as increased areas under irrigation or hectares under new technologies, are easier to measure and more attributable to a programme, but leave less room for innovation and experimentation. In addressing the complexities of different rural worlds, results-based programmes already show their benefits in targeting specific groups. However, a more systematic assessment of the inter-linkages between the rural worlds can yield additional benefits for the implementation of results-based approaches.
Keywords: 330; Wirksamkeit und Evaluierung; Landwirtschaft und ländliche Entwicklung